Correlation of implementation of principles and functions of management in hospitality business - Knežević, Natalija; Grubor, Biljana; Kalenjuk Pivarski, Bojana; Šmugović, Stafan; Banjac, Maja; Radivojević, Goran (Turizam, 2021)
Hospitality organizations of today keep up with the trends to remain competitive in a changeable market. For that reason, organizations must continuously work on their development and sustainability, and quality and good management is a precondition for successful business operations. Management is a universal process implemented in different production and service activities of the economy and different organizations regardless of the size and structure. Accordingly, food and beverage managers in hospitality have a task to combine fundamental principles and functions of management to achieve the company goals and bring success to the business. The subject of this paper is a review of principles and functions of management with the aim to make a correlation between individual functions and principles and their codependence in a restaurant business.